PERAN PEMBELAJARAN BERBASIS PROYEK DALAM MENGEMBANGKAN SOSIAL EMOSIONAL ANAK USIA 5–6 TAHUN DI TK RESTU AMANDA - Titin Astuti; Ida Ermiana; Darmiany (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the role of Project-Based Learning (PjBL) in developing social-emotional skills in children aged 5–6 years at TK Restu Amanda. Using a qualitative case study approach, data were collected through participatory observation, semi-structured interviews with teachers, and documentation of project activities. The research focused on a project titled “My Mini Garden at School,” which engaged children in collaborative planning, planting, nurturing, and reflecting on their plants. Findings indicate that PjBL enhances children’s self-confidence, collaboration, emotional regulation, and social communication. Children actively participated in group discussions, shared responsibilities, managed frustration, and expressed pride in their accomplishments. The teacher acted as a facilitator, providing scaffolding and promoting meaningful interactions within the zone of proximal development. These results suggest that PjBL is an effective pedagogical approach for fostering social-emotional learning (SEL) in early childhood education, particularly when adapted to local contexts and combined with authentic, hands-on experiences. The study contributes both theoretically and practically by demonstrating the integration of constructivist and socio-cultural learning principles in early childhood settings.